PENGARUH PENERAPAN MANAJEMEN KUALITAS TERHADAP KINERJA ORGANISASI DENGAN KINERJA OPERASIONAL SEBAGAI VARIABEL MEDIASI PADA USAHA KECIL MENENGAH DI KABUPATEN KUANTAN SINGINGI - Hakim Fikrul; Restu Restu; Daulay Nauli Iwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of the implementation of quality management (X) on organizational performance (Y) by mediating operational performance (M) in Small and Medium Enterprises (UKM) in Kuantan Singingi Regency. The population in this study were all SMEs in the processing industry sector that had received PP-IRT certificates in Kuantan Singingi Regency, totaling 57 SMEs. Primary data were collected using a questionnaire as an instrument to prove the results of the study. To test the hypothesis in this study was to use SEM-PLS with the help of the Smart-PLS program. The sampling technique that has been chosen is the census method (57 SMEs in the manufacturing sector who have received PP-IRT Certificates in Kuantan Singingi Regency). The results of this study indicate that: 1) There is a positive and significant effect of the application of quality management on operational performance, 2) There is a positive and significant effect of the application of quality management on organizational performance, 3) There is a positive and significant effect of operational performance on organizational performance, 4) There is a the positive and significant influence of the application of quality management on organizational performance mediated by operational performance of SMEs in the processing industry sector that have received PP-IRT Certificate in Kuantan Singingi Regency.Keywords: Quality Management, Operational Performance, Organizational Performance